Peukateun at Rapa'i Geurimpheng in Ukee Village Geulumpang Baro District Pidie Regency - Ahmad Syai (International Conference on Science, Education, and Technology, 2021)
Rapa'i geurimpheng is a type of traditional Acehnese music performance. This musical performance is performed by men with a cast of 8-12 people, 3-5 accompaniments and 1 syech who sounds melodious as a vocalist. The players who number 8-12 people as music presenters with attractions must learn extra to be able to put on a good show. The purpose of this study was (1) to review"Peukateun" on Rapa'i Geurimpheng in Ukee Village geulumpang district of Baro Pidie regency" and (2) character education carried out as an effect of "Peukateun" on rapa'i geurimpheng training in ukee village geulumpang baro district Pidie district. The method used in this study is qualitative descriptsiveness that is interpretive with a cultural approach. The results showed that "Peukateun" on rapa'i geurimpheng in ukee village was highly acclaimed and correctly became a "game" for a show. Character planting is formed as a result of the"peukateun" carried out by this group. The players have good personalities, are responsible, respect each other, and can maintain their culture.